Exploring the relationship between development and disasters : Bir Hospital as a microcosm of this relationship : a thesis presented in partial fulfillment of the requirements for the degree of Masters of Philosophy in Development Studies at Massey University - Patton, Robert (Massey University, 2001)
The question is asked as to whether there is a relationship between development and disasters. To answer this question these two words must first be defined. The simplest definitions are that development is good change and a disaster is the result of an interaction between an event and a vulnerable community. From the literature it was found that the relationship between development and disasters fell into two broad categories; a financial relationship and a contributory relationship. The financial relationship was primarily that disasters diverted funds away from development. This occurred in two ways. One is that funds earmarked for development were re-directed into relief following a disaster. The other is that a disaster can destroy past development investment in a community and reduce community potential for future development. The contributory relationship was that development could either reduce or increase a community's vulnerability to a disaster-producing event. A 1998 vulnerability assessment report of the Kathmandu Valley in Nepal identified that Bir Hospital was vulnerable to the impact of an earthquake. Bir Hospital was taken as a case study to demonstrate the contributory relationship between development and disasters. This case study identified whether past development activities had contributed to this vulnerability and could future development activities reduce the vulnerability of Bir Hospital. In preparation for the detailed assessment of Bir Hospital the experiences of other hospitals in disaster situations was researched and standards for measuring a hospital's vulnerability were identified. The outcome of the vulnerability assessment of Bir Hospital was that the hospital is extremely vulnerable to the impact of an earthquake and that development activities in the past had contributed to this. There is strong potential for future development to reduce the vulnerability of the hospital. The overall conclusion is that there is a definite relationship between development and disasters. This relationship can be either positive or negative. In recognition of this relationship it is recommended that development practitioners and disaster managers work closely together.
Irreqular Pagination Page 129 is missing
Keywords: Nepal -- Kathmandu Valley; Community development; Hospitals; Earthquakes -- Planning